Sistem Prediksi untuk Menentukan Jumlah Pendaftaran Mahasiswa Baru pada Unversitas Catur Insan Cendekia Menggunakan Metode Least Square - Muhadzdzab, Humam; Asfi, Marsani; Putri, Tiara Eka (Jurnal Informatika Universitas Pamulang, 2020)
The prediction system for determining the number of prospective new students aims to make decisions and prioritize how many new students will be accepted and as a means of enthusiasts for the most study program trends each year, in making a prediction system, a method for good calculations is needed, so it is necessary method for the prediction system. This prediction system uses the Least Square method for the calculation of prediction results for system design carried out with an object-oriented approach using UML. The computer-based system built is web-based using the programming languages PHP and MySQL. From this research, the Least Sqaure method can be implemented to calculate predictions to determine the number of prospective new student registrations and to help the secretariat staff in the admissions section to find out the most interest in the study program each year.